A Clinical Trial of Wrist-Ankle Acupuncture for Abirritation during High-Intensity Focused Ultrasound Treatment of Adenomyosis - Chenning Liu; Xiaoyang Lin; Yuhui Liu; Meiduo Zhao; Qiuxian Shen; Li Tang; Yanqin Wang; Xiaojuan Zhou; Huituan Liu; Hongjin Yu (IMR Press, 2022)
Background: Wrist-ankle acupuncture (WAA) has promising analgesic effect during high-intensity focused ultrasound (HIFU), but evidence-based clinical test is scarce. The purpose of this research is to assess the efficacy of WAA for relieving pain during HIFU treatment of adenomyosis. Methods: Fifty-eight patients with adenomyosis treated with HIFU were enrolled in this study. Among them, 30 patients chose the WAA group, and the others selected the pethidine injection. The visual analog scale (VAS) pain score was recorded to assess the pain during HIFU before and after analgesic therapy. The VAS at 10 min, 30 min and 1 h after analgesic therapy, and the adverse effects, were noted and calculated to compare these two approaches. Results: The median pain score in the WWA group at 10 minutes was 6 [6, 7], which was higher than that in the control group it was 5 [4, 6] (p < 0.001). At 30 min and 60 min, the pain scores were 5 [4, 6] in the WAA group and in the control group. The statistically significant differences were not found in pain relief scores at 30 or 60 min (p > 0.05). No side effects were observed in the WAA group. Conclusions: WAA is a safe and easily available technique to reduce the pain during HIFU treatment, with no severe effects. Thus, it can be widely used and promoted in clinical practice.